Pemanfaatan CARRD untuk topik ,keluarga' pada pembelajaran bahasa jerman di SMA Negeri 1 Batu - Suhendra, Asmara Putri; Sobara, Iwa (Fakultas Sastra, 2023)
This study was carried out to examine the use of CARRD as a learning medium in German lessons, particularly on the subject of "Family". This study took place in Class XI Lintas Minat at SMA Negeri 1 Batu. The method used in this research is descriptive-qualitative. The Data were taken from observation forms completed by two observers. In addition, the questionnaires were distributed to the students. There were a total of 20 students who participated in this study. The research was successful and the students were able to access the website provided by the researchers. The students were also active during the activity and all of the students were able to use CARRD well. Almost all students indicated that the visualization on CARRD was very appealing. CARRD also contains many features that can support teaching and learning activities.